Upaya Bersama dalam Mengatasi Penyebaran Covid-19 Kecamatan Sungai Apit - Safrizal Safrizal; Rudi Hartono; Futri Aslamiah; Fani Fardila; Saputra Ramahendra; Neni Hermita (Journal of Community Engagement Research for Sustainability, 2021)
This volunteer activity is carried out with the aim of increasing public awareness about Covid-19. In Teluk Batil Village, there are still people who do not use masks regularly and maintain a distance according to the health protocol directions when outside their homes. This is because there is still a lack of understanding about the dangers that will arise from the virus. This activity started with consulting the sub-district secretary and village head, distributing new normal brochures, educational videos for children, distributing masks, providing handwashing facilities, hand sanitizers, and some of the activities we carried out. With the hope that the community can maintain health starting from themselves and the surrounding environment as an effort to break the chain of the spread of Covid-19.